2x + 3y = -4
x-2y = 5
Write x as x= 5+2y
Sub this back in the first equation
2(5 + 2y) + 3y = -4
10 + 4y + 3y = -4
7y = -4 - 10 = -14
y = -2
x = 5 + 2y = 5 + (-4) = 1
Check this:
2x + 3y = -4
2(1) - 3(-2) = -4
2 - (6) = -4 Good!
2007-01-10 05:37:26
·
answer #1
·
answered by MamaMia © 7
·
1⤊
0⤋
2x + 3y = -4 and
x - 2y = 5. Solve by substitution?
x - 2y = 5 gives
x = 5 + 2y = 2y + 5 Now substitute 2y + 5 in the first equation
2(2y + 5) + 3 y = -4 Now simplify
4y + 10 + 3y = -4
4y + 3y = -4 - 10
7y = -14
y = -2 Now go back to the second equation and substitute -2 for y
x - 2(-2) = 5
x + 4 = 5
x = 5 - 4
x = 1
HTH
Charles
2007-01-10 13:42:41
·
answer #2
·
answered by Charles 6
·
0⤊
0⤋
2x + 3y = - 4- - - - -Equation 1
x - 2y = 5- - - - - - -Equation 2
- - - - - - - - -
Substitution Method equation 2
x - 2y = 5
x - 2y + 2y = 5 + 2y
x = 5 + 2y
The answer is x = 5 + 2y
Insert the x value into equation 1
- - - - - - - - - - - - - - - - - - - - - -
2x + 3y = - 4
2(5 + 2y) + 3y = - 4
10 + 4y + 3y = - 4
10 + 7y - 10 = - 4 - 10
7y = - 14
7y/7 = - 14/7
y = - 2
The answer is y = - 2
Insert the y value into equation 1
- - - - - - - - - - - - - - - - - - - - --
2x + 3y = - 4
2x + 3(- 2) = - 4
2x + (- 6) = - 4
2x - 6 = - 4
2x - 6 + 6 = - 4 + 6
2x = 2
2x/2 = 2/2
x = 1
The answer is x = 1
Insert the x value into equation 1
- - - - - - - - - - - - - - - - - - - - -
Check for equation 1
2x + 3y = - 4
2(1)+ 3(- 2) = - 4
2 + (- 6) = - 4
2 - 6 = - 4
- 4 = - 4
- - - - - - -
Check for equation 2
x - 2y = 5
1 - 2(- 2) = 5
1 - (- 4) = 5
1 + 4 = 5
5 = 5
- - - - - - - - - - -
The solution set is { 1, -2 }
- - - - - - -s-
2007-01-10 15:13:36
·
answer #3
·
answered by SAMUEL D 7
·
0⤊
0⤋
2x + 3y = 4
x - 2y = 5 solve for x ; x = 2y + 5
2( 2y + 5 ) + 3y = 4
4y + 10 + 3y = 4
7y + 10 =4
7y = - 6
y = - 6/7
if that is the value of y then x = 2(-6/7) +5
work that out and that is the value of x.
Using matrices is an easier method of solving systems.
2007-01-10 13:39:13
·
answer #4
·
answered by Ray 5
·
0⤊
0⤋
First solve the second equation for x or y. I will solve for x
x-2y=5
x=5+2y because u added -2y to both sides.
Then substitute this equation into x for the first equation, like this.
2(5+2y)+3y= -4
10+4y+3y= -4
10+7y= -4
7y=-14
y= -2
You have now gotten the y answer. Now, you need to substitute the y answer into the equation to get the x answer.
x=5+2y
x=5+2(-2)
x=5-4
x=1
So your answers for the solution set are (1,-2)
2007-01-10 13:43:20
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
by substitution it means y or x in one equation to be subtituted in the other equation.
lets say
2x+3y=-4---------------eqn 1
x-2y=5-------------------eqn 2
from eqn 2, x=5+2y ------eqn 2b
and since the x and the y in eqn 1 and 2 are the same, x in eqn 1 can be subtituted with the x in eqn 2b
2( 5+2y) + 3y= -4
10 +4y + 3y = -4
7y = -10 -4
7y = -14
y = -14/7
y = -2
from eqn 2b x= 5 + 2y and y = -2
therefore x = 5 + 2 (-2)
x = 5 - 4
x = 1
x=1 and y = -2
2007-01-10 13:59:35
·
answer #6
·
answered by yason 2
·
0⤊
0⤋
2x+3y=-4
x-2y=5=>x=5+2y
2(5+2y)+3y=-4=>10+4y+3y=-4=>7y=-14=>y=-2
x=5+2*(-2)=>x=1
hope this helps!
2007-01-10 13:58:52
·
answer #7
·
answered by teo 1
·
0⤊
0⤋
x = 1
y = -2
2007-01-10 13:38:18
·
answer #8
·
answered by mathlete1 3
·
0⤊
1⤋